Determinan Produksi Pada Perkebunan Kelapa Sawit Di PT. Bumitama Gunajaya Agro - Novan Dwi Ari Wijaya; Ida Budiarty (Shofanah Media Berkah, 2023)
This research aims to determine the influence of land area, workforce, and fertilizers on the production of oil palm plantations in PT. Bumitama Gunajaya Agro. The method used in this study is a quantitative approach that focuses on numerical data analysis, which is then statistically analyzed accordingly. The location used in this research consists of 60 units of oil palm plantations. These plantations are owned by PT. Bumitama Gunajaya Agro in 2021, including their self-owned plantations and plasma program plantations. The technique of analysis used in this study is multiple linear regression test using Eviews 12 software, which includes Partial Test (T-Test) and Simultaneous Test (F-Test). The results of partial estimation conducted showed that the variables of land area, workforce, and fertilizers have a positive and significant effect on the production of fresh fruit bunches of oil palm plantations in PT. Bumitama Gunajaya Agro. Variables of land area, workers, and fertilizers together have a positive and significant effect on the production of fresh fruit bunches of oil palm plantations in PT. Bumitama Gunajaya Agro.